2019
DOI: 10.1108/jcefts-11-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of capital structure on profitability and stock returns

Abstract: PurposeThe purpose of this study is to examine the factors that influence capital structure, profitability and stock returns and the relationship between capital structure, profitability and stock returns. The endogenous variables in this study are capital structure, profitability and stock returns, whereas the exogenous variables are firm size, growth opportunity, tangibility, liquidity, volatility and uniqueness.Design/methodology/approachThe population used is a company that is listed on the compass index 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
2
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 47 publications
(84 reference statements)
9
29
2
23
Order By: Relevance
“…The results of this study prove that the company will increase the proportion of debt in capital structure decisions when the size of the company is getting bigger as well. The results of this study are consistent with the research conducted by Widodo (2014); Gomez et al (2014); Chandra et al (2019), who concluded that firm size has a positive and significant influence on the decision to use corporate debt in the capital structure. The positive and significant effect in this study explains that firm size is a factor that is considered related to the level of debt proportion in capital structure decisions.…”
Section: Effect Of Firm Size On Capital Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study prove that the company will increase the proportion of debt in capital structure decisions when the size of the company is getting bigger as well. The results of this study are consistent with the research conducted by Widodo (2014); Gomez et al (2014); Chandra et al (2019), who concluded that firm size has a positive and significant influence on the decision to use corporate debt in the capital structure. The positive and significant effect in this study explains that firm size is a factor that is considered related to the level of debt proportion in capital structure decisions.…”
Section: Effect Of Firm Size On Capital Structuresupporting
confidence: 92%
“…A large company size will find it easier to get funding from outside parties than a small company considering the ability and level of risk (Sofat & Singh, 2017). Research Dewi and Ramli (2016); Chandra et al (2019) state that company size has a positive effect on capital structure. In contrast to the research results of Indriani and Widyarti (2013); Alipour, et al (2015); Sofat and Singh (2017) stated that company size has a negative effect on capital structure.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study are in line with research by Niar (2019), which states that investment decisions do not influence profitability in manufacturing companies in Indonesia. And in line with the research by Chandra et al (2019) on company data on Kompas 100, they conclude that investment decisions do not affect company profitability. These findings indicate that the return on investment obtained by investors is not in the short term but the long term and is full of high levels of uncertainty.…”
Section: Effect Of Investment Decisions On the Financial Performancesupporting
confidence: 69%
“…Prior studies have implemented several ratios to measure firm's profitability, for example, return on assets (Doğan, 2013;Vătavu, 2015;Karadeniz and Kaplan, 2016;Chandra et al, 2019), return on equity (Salim and Yadav, 2012;Vătavu, 2015;Le and Phan, 2017) and the ratio of operating profitability to total assets (Kebewar, 2013;Karadeniz and Kaplan, 2016;Detthamrong et al 2017). This study uses the aforementioned ratios to proxy for profitability.…”
Section: Financial Performance (Profitability)mentioning
confidence: 99%